Gender-age peculiarities of smoking and diabetes mellitus role in the development of myocardial infarction in patients with arterial hypertension - Anna V. Aksenova (IP Morozov P.V., 2021)
Arterial hypertension (AH), smoking and type 2 diabetes mellitus (T2DM) are the risk factors for the development of myocardial infarction (MI). Their age and gender peculiarities of AH have been studied only in a small number of epidemiological studies.